Water, investment and food security - Chartres, Colin J. (2011)
Water resources are already very scarce. With further demand from population growth, dietary changes, biofuel production, urbanisation and climate change, it will be extremely difficult to find enough supply to enable an increase in global food production by 70 per cent. There are, however, potential solutions that involve increasing water productivity, improved water storage, more irrigation and re-using waste water. But current investment levels in overseas development aid and spending at country level are unlikely to be sufficient to ensure food security in the relatively short- term, let alone by 2050, when the global population is forecast to be nine billion. This article describes some of the issues that have to be faced to deliver food security and overcome water scarcity, and how these improvements can be achieved through a combination of science, policy and investment.